The German version of the helping alliance questionnaire: psychometric properties in patients with persistent depressive disorder - Eich, Hannah Sophie; Bailer, Josef (BMC psychiatry, 2018)
The Helping Alliance Questionnaire (HAQ) is a frequently used and highly relevant instrument to assess the therapeutic alliance. The questionnaire was translated into German by Bassler and colleagues (1995) and is available for patients (HAQ-P) and therapists (HAQ-T). Whereas the HAQ-P has been tested regarding psychometrics, the HAQ-T has not. This study aimed at further investigating the psychometric properties of both the HAQ-P and HAQ-T. We hypothesized that the instrument is reliable and shows factorial as well as convergent validity.
Gesehen am 08.06.2018